European integration of Ukraine as a factor of transformation of legal practice (theoretical and legal aspect) - Artem Beresten (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2023)
The article discusses the directions for development of legislation that would correspond to the Constitution of Ukraine and its recognized legal principles, which are closely linked to the enhancement of the role of law in the legal system of Ukraine. In the context of Ukraine's European integration processes, as a candidate state for EU membership, the main factors influencing the reform of Ukraine's legal system are analyzed, and priorities for the development of legislative initiatives are identified, including those relating to the problems of organizational and legal support for the development of judicial cooperation in civil and criminal cases, using international and bilateral documents based on the principles of legal certainty and the right to a fair trial. Changes to the legislation "On National Minorities (Communities) of Ukraine" and laws for the implementation of the rights and freedoms of individuals and citizens of Ukraine in accordance with generally recognized norms of international law and European conventions ratified by Ukraine are also discussed. Special attention is paid to the principles of development and improvement of legislation, namely the principles of the rule of law, strict adherence to constitutional provisions, democracy, social expediency, scientific justification, systematic and coordinated legislative activity, the interrelationship and interaction of legislative acts, and the priority of generally recognized norms and principles of international law over national legislation.